1966
DOI: 10.1007/bf00423020
|View full text |Cite
|
Sign up to set email alerts
|

Micro-angiopathie dans l'appareil digestif de sujets atteints de diab�te pr�coce et de longue dur�e

Abstract: Summary.The digestive tract has been examined by light microscopy in 17 subjects with diabetes of early onset, long duration and with various causes of death, in 6 "normal" controls and 10 controls with uremia and/ or hypertension. In the diabetics grave lesions were demonstrated to a large extent in the capillaries and venules of the oral mucosa, and in small arteries and arterioles in the gastrointestinal tract (from the oesophagus to rectum). The capillary and venular lesions were similar to those earlier d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The NO-sensitive microelectrode cannot discriminate between a hyperglycemia-mediated decrease in NO production or an increase in NO destruction mediated by oxygen radicals known to be formed during acute hyperglycemia (4,9). However, our finding that basal [NO] decreased and endotheliumdependent production of NO could not be increased during acute hyperglycemia is consistent with the deleterious actions of acute hyperglycemia on endothe-lial cell structure (1,17,21) and endothelial regulation of arteriolar tone (4,7,15,23).…”
Section: H1518supporting
confidence: 70%
See 2 more Smart Citations
“…The NO-sensitive microelectrode cannot discriminate between a hyperglycemia-mediated decrease in NO production or an increase in NO destruction mediated by oxygen radicals known to be formed during acute hyperglycemia (4,9). However, our finding that basal [NO] decreased and endotheliumdependent production of NO could not be increased during acute hyperglycemia is consistent with the deleterious actions of acute hyperglycemia on endothe-lial cell structure (1,17,21) and endothelial regulation of arteriolar tone (4,7,15,23).…”
Section: H1518supporting
confidence: 70%
“…In streptozotocininduced diabetic rats, brain endothelial cells became morphologically abnormal within 3 wk of chronic hyperglycemia, and ϳ20% of the cells appeared to be dying (17). Similar changes in endothelial cell morphology have been described in severely diabetic humans (1). In vitro studies using insulin-dependent diabetic rat arterioles (16) and rabbit aorta (24) have demonstrated that 6-10 wk of chronic hyperglycemia caused a significant suppression of endothelium-mediated vasodilation.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The patchy nature of diabetic MA has been observed in the oral mucosa where abnormal vessels bordering on otherwise normal areas have been noted. 15 Furthermore, the autonomic neuropathy that involves the vagus and the sympathetic nervous system, which is assumed to play an important role in the pathogenesis of the gastroenteropathy, is frequently patchy. 2 The second probable explanation is that MA requires a long period of time to develop to such a degree that it is visible by light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This later rationale is supported by the fact that patients with well documented diabetic angiopathy have a long history of poorly controlled diabetes mellitus. 15 Capillary basement membrane thickening is not unique for diabetes mellitus, and has been postulated to be a nonspeci®c reaction of the microvasculature against noxious stimuli. 16 Similar angiopathic changes can be seen in ageing, systemic lupus erythematosus, dermatomyositis, intermittent claudication, gout, several neuromuscular disorders, congestive heart failure, Hashimoto's thyroiditis and myxoedema; 10 however, in these conditions such changes are less pronounced and slower to develop.…”
Section: Discussionmentioning
confidence: 99%